1990
DOI: 10.1042/bj2710791
|View full text |Cite
|
Sign up to set email alerts
|

Inositol phosphate release and steroidogenesis in rat adrenal glomerulosa cells. Comparison of the effects of endothelin, angiotensin II and vasopressin

Abstract: Endothelin has steroidogenic activity in adrenal glomerulosa cells, as do two other vasoconstrictor peptides, angiotensin II and vasopressin. The steroidogenic activities of angiotensin II and vasopressin are probably mediated via the phosphatidylinositol-turnover pathway and associated changes in cytosolic Ca2+ concentration. Endothelin caused a steroidogenic response, which was small compared with that to angiotensin II and quantitatively similar to the vasopressin response. Cytosolic free Ca2+ responses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 53 publications
3
13
1
Order By: Relevance
“…7) (17, 126, 290, 479, 567, 611, 814). This stimulatory effect of ET peptides is relatively small compared with that of ANG II, based on studies in which ET-1 was systemically administered in vivo (480), in dispersed rat zona glomerulosa cells (478, 836), or using human adrenal slices (875). In addition, ET-1 may potentiate ANG II actions in the adrenal.…”
Section: Endothelin and Humoral Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…7) (17, 126, 290, 479, 567, 611, 814). This stimulatory effect of ET peptides is relatively small compared with that of ANG II, based on studies in which ET-1 was systemically administered in vivo (480), in dispersed rat zona glomerulosa cells (478, 836), or using human adrenal slices (875). In addition, ET-1 may potentiate ANG II actions in the adrenal.…”
Section: Endothelin and Humoral Systemsmentioning
confidence: 99%
“…In rat adrenal glomerulosa cells, ET-1 increased [Ca 2+ ] i (836). ET B activation increased [Ca 2+ ] i in rat zona glomerulosa cells, at least in part, through intracellular release; the response was independent of dihydropyridine-sensitive Ca 2+ channels (19).…”
Section: Endothelin and Humoral Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that ET is able to stimulate PI turnover in rat adrenal cortex (Woodcock et al, 1990) and adrenal medulla (Garrido and Israel, 1997). Furthermore, phosphoinositide (PI) turnover induced by the activation of ET receptors, is involved with the catecholamines secretagogue activity elicited by ET-related peptides (Belloni et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…For example, carbachol (a stable acetylcholine receptor agonist), endothelin-1, sphingosine 1-phosphate, and vasopressin have all been reported to activate phosphoinositide hydrolysis to stimulate adrenocortical cell steroid hormone production (Kojima et al 1986, Woodcock et al 1986, Woodcock et al 1990, Bollag et al 1992, Andreis et al 2001, Delarue et al 2004, Brizuela et al 2006. Neuropeptide B has also been shown to increase IP 3 levels in adrenal fasciculata/ reticularis cells, and the PLC inhibitor U73122 reduced neuropeptide-elicited cortisol production (Mazzocchi et al 2005).…”
Section: Phospholipase Cmentioning
confidence: 99%